An Investigation of Temperature and Wind Impact on ACSR Transmission Line Sag and Tension - Abbasi, M. Z.; Noor, B.; Aman, M. A.; Farooqi, S.; Karam, F. W. (Engineering, Technology & Applied Science Research, 2018)
Power transmission is mainly based on overhead transmission lines with conductors being supported by transmission towers. Transmission lines are subjected to environmental stress (temperature changes, winds, snow etc), have an impact on the surrounding areas (visual pollution, building restrictions) and experience heavy losses due to resistive, magnetic and capacitive effects. Thus, proper modeling and installation of these conductors are necessary. The conductors are generally installed in a catenary shape to minimize the capacitive effects and to balance the tension. This paper presents an investigation on the sag and tension behavior under different temperature and wind of ACSR (Aluminum Conductor-Steel Reinforced) lines. Four different cases of temperature and wind are tested to calculate sag and tension. Simulation setup is done in ETAP (electrical transient and analysis program). Results are recorded and discussed.